Analisis Kualitas Layanan Program Praktek Kerja Lapangan (PKL) Mahasiswa Jurusan Tata Boga Politeknik Negeri Balikpapan Tahun 2015 - Syahrul Karim; Yogiana Mulyani; Tuatul Mahfud (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2016)
AbstrackBalikpapan East Kalimantan as an economic barometer Kalimantan even continue to grow especially in the sector of tourism support the hospitality industry. End of 2015, the number of hotels in Balikpapan 75 units. This figure rose to 80 units in 2016. (Disporabudpar Balikpapan, 2015). Hotel presence contributes directly to employment. Not only Balikpapan, but a number of cities in East Kalimantan even outside of Borneo, such as Java and Sulawesi. State Polytechnic Balikpapan is the only campus in Kalimantan, which organizes lectures majoring in culinary Diploma III. Every year 40 students graduated / I since 2013. One of the flagship program of the Department of cookery is the delivery service Job Training (PKL) in the hospitality industry, catering and restaurant for six months. PKL service student success cookery State Polytechnic Balikpapan should be measured by various indicators of services during the performance management vendors by involving the industry as a user of the service. From the results of recent research shows that the quality of student services PKL majors Catering, Polytechnic of Balikpapan in 2015 rated satisfactory by the street vendors (the hotel industry and catering) for the nine attributes of service that is dependability, attitude, personality, quantity, adaptability, quality, Job Knowledge and grooming has average ratings of at least 3.2 (in the satisfactory category). While three other service attributes attendance, initiative, and discipline unsatisfactory. Has a sufficiently low value or below 3.2 (in the satisfactory category). This is in line with the IPA matrix analysis results where there are four elements that are considered important by the hotel management but did not provide the satisfaction of attendance, Initiative, discipline and job knowledge. Key Words :service attributes, trainee, expectations, satisfaction AbstrakBalikpapan sebagai barometer ekonomi Kalimatan Timur bahkan Kalimantan terus tumbuh terutama di sektor industry pendukung pariwisata yakni perhotelan. Akhir tahun 2015, jumlah hotel di Balikpapan 75 unit. Angka ini naik menjadi 80 unit di tahun 2016. (Disporabudpar Balikpapan, 2015). Keberadaan hotel memberikan andil secara langsung terhadap penyerapan tenaga kerja. Tidak hanya Balikpapan, namun sejumlah kota di Kaltim bahkan di luar Kalimantan, seperti Jawa dan Sulawesi. Politeknik Negeri Balikpapan merupakan satu satunya kampus di Kalimantan yang menyelenggarakan perkuliahan jurusan tata boga Diploma III. Setiap tahun meluluskan 40 mahasiswa/I sejak tahun 2013. Salah satu program unggulan dari jurusan tata boga adalah penyelenggaran layanan Praktek Kerja Lapangan (PKL) di industry perhotelan, catering dan restaurant selama enam bulan. Keberhasilan layanan PKL mahasiswa/I tata boga Politeknik Negeri Balikpapan harus diukur dengan berbagai indicator layanan selama melaksanakan PKL dengan melibatkan management industry sebagai pengguna layanan. Dari hasil penelian menunjukan bahwa kualitas layanan mahasiswa PKL jurusan Tata Boga, Politeknik Negeri Balikpapan 2015 dinilai memuaskan oleh pengguna PKL (industri hotel dan catering) untuk 9 atribut layanan yakni dependability, attitude, personality, quantity, adaptability, quality, Job Knowledge dan grooming yang memiliki rata rata penilaian minimal 3.2 (dalam kategori memuaskan). Sedangkan 3 atribut layanan lainnya attendance, iniciative, dan discipline kurang memuaskan. Memiliki nilai yang cukup rendah atau dibawah 3.2 (dalam kategori memuaskan). Ini sejalan dengan hasil analisi matrix IPA dimana terdapat empat element yang dianggap penting oleh managemen hotel namun belum memberikan kepuasan yakni attendance, iniciative, discipline dan job knowledge.Kata Kunci : kualitas layanan, praktek kerja lapangan, harapan, kepuasan